Analisis Overreaction Pada Saham-Saham Lq-45 Di Bursa Efek Indonesia - Joshua Duta Wacana dan Carunia Mulya Firdausy (Universitas Tarumanagara, 2019)
Behavior of investors as individuals in taking attitudes and actions there are different in addressing an information. Market participants do not all consist of rational and emotional people. In some cases, there are investors who behave excessively in response to information by spontaneously selling stocks when the market moves beyond expectations or buys newly profitable stocks regardless of the fundamental valuation of the stock price. Such deviations include the phenomenon of January Effect, the phenomenon of size effect and day of the week. Overreaction hypothesis is one of the deviations that occur in the capital market. The results showed LQ-45 stocks on the Indonesia Stock Exchange despite several overreaction symptoms but showed less significant results. Based on this, it can be concluded that there is no overreaction anomaly in the stock market in Indonesia Stock Exchange especially on LQ-45 stocks in the period of 2013-2015. The results also show that contrarian strategies can not be performed to obtain an abnormal return.